Mamki – najemne karmicielki w świetle literatury poradnikowej z drugiej połowy XIX i początku XX wieku - Nawrot-Borowska, Monika (Biuletyn Historii Wychowania, 2014)
Wet nurses, i.e. hired breast-feeders of babies, were the subject matter of this research. It aims to systematize the advice that was formulated on the pages of “how-to” books regarding the search for, recruitment, and treatment of wet nurses in the homes of one’s charges. The specific duties of wet nurses that were especially expected of them are determined, as well as the errors most frequently committed in their performance, which the authors of how-to books described at length, in order to warn mothers against the incompetence of paid breast-feeders. A comparison of the views of authors of “how-to” books over nearly 70 years will allow us to determine a possible evolution of views regarding wet nursing. The “how-to” books on health, hygiene, and education from the second half of the 19th century and the early 20th century (the period approximately from 1850-1918), published in Polish areas and addressed mainly at families, especially mothers, form the source material for the research. The use of this type of literature will allow us to reconstruct the promulgated image of wet nursing without broader reference to providing help for them, which is worth confronting with the “how-to”  recommendations, attempting to determine whether, and to what extent, they were reflected in everyday life (e.g. using epistolary or archival sources, and memoirs). Nevertheless, the authors of “how-to” books also referred to the practice of tending infants and young children, criticizing inappropriate behaviour of wet nurses, while the recommendations formulated by them were to remedy inappropriate behaviour occurring in reality. The issue of wet nursing has not hitherto been analysed in detail in Polish historiography. In recent years, though, a few texts or papers in which one can find more or less extensive information (the less extensive ones predominate) related to breastfeeding by wet nurses in the Polish areas in the Middle Ages, the period of Old Poland, or the partition period, have been published. Thus, it seems even more reasonable to explore this issue, which will help to fill a gap in the development of the history of breastfeeding, nursing, and tending infants and small children.